Skrining dan Efektivitas Metabolit Sekunder Mikania micrantha pada Gulma Jajagoan serta Dampaknya terhadap Padi Sawah - Alridiwirsah Alridiwirsah; Koko Tampubolon; Fransisca Natalia Sihombing; Wan Arfiani Barus; Irna Syofia; Tengku Boumedine Hamid Zulkifli; Zavandri Purba (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
Secondary metabolites from Mikania micrantha could be expected to control barnyardgrass (Echinochloa crus-galli) characteristics and have an effect on lowland rice. This research was aimed to screening of secondary metabolites in M. micrantha extract, obtaining the greater extract concentration in suppressing the barnyardgrass growth, and determine the impact on the lowland rice characteristics. This method used was Randomized Completely Block Design in non-factorial within the concentration rates of M. micrantha extract using ethanol 96% (0%; 20%; 40%; 60%; 80%; 100%, and herbicide 2,4-D dimethylamine at the dose of 1 l ha-1 as a comparison). Lowland rice and barnyardgrass characteristics were analyzed using F-test and followed by DMRT at 5% with SPSS software. The result showed that M. micrantha had secondary metabolites include alkaloids, flavonoids, and tannins. The concentration at 20 to 100% significantly decreased the fresh- and dry-weight of barnyardgrass with the highest suppressing found in 60% concentration by 65.91% and 67.92%, respectively compared to un-sprayed. The concentrations at 20% and 60% were classified as inhibiting the growth biomass of barnyardgrass. The concentrations at 20%, 60%, and 80% can still encourage the tillers growth of lowland rice. An extract concentration of M. micrantha at 20% can be applied to inhibit the growth of barnyardgrass biomass and stimulate the lowland rice tillers.